2006
DOI: 10.1158/0008-5472.can-06-1894
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Responses to Cellular Stress

Abstract: Recent work has begun to explore the instrumental role that small noncoding RNA species, particularly microRNAs (miRNA), have both in classifying human tumors and in directing embryonic development. These studies suggest that developmental programs in essentially all organisms studied are set, in part, by varied expressions of miRNAs and that neoplasia is characterized by altered expression of miRNAs.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
231
0
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(242 citation statements)
references
References 41 publications
10
231
0
1
Order By: Relevance
“…In addition, miRNAs have also been suggested to be involved in the CSR; however, a few fundamental questions remain largely unanswered (Cimmino et al 2005;Leung et al 2006;Marsit et al 2006;Kulshreshtha et al 2007;Leung and Sharp 2007;Babar et al 2008). First, which specific miRNAs do cells express when exposed to stress?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, miRNAs have also been suggested to be involved in the CSR; however, a few fundamental questions remain largely unanswered (Cimmino et al 2005;Leung et al 2006;Marsit et al 2006;Kulshreshtha et al 2007;Leung and Sharp 2007;Babar et al 2008). First, which specific miRNAs do cells express when exposed to stress?…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies suggest that miRNAs participate in the CSR (Cimmino et al 2005;Leung et al 2006;Marsit et al 2006;Kulshreshtha et al 2007;Leung and Sharp 2007;Babar et al 2008). However, several fundamental questions remain unanswered concerning the role that miRNAs may play in these mechanisms: First, which specific miRNAs are expressed by cells exposed to stress?…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Wang et al (2009) actually examined the effects of ethanol on in vivo mouse brain development and found that at least 14 different miRNAs were misexpressed. These included, in addition to miR-9 (as found by Sathyan et al, 2007), miR-10a and miR-200a (as in DKO cells) as well as miR-145 (as in FAD cells) (Han et al, 2007;Marsit et al, 2006). These embryos also displayed, amongst other abnormalities, defects in neural tube closure starting at concentrations of 2.0 mg/ml of ethanol.…”
Section: Mirna Misregulation and Ntdsmentioning
confidence: 92%
“…Although DHFR did not turn up any significant hits in the database search and miR-24 was not considered an miRNA of interest in this review (neither it is neural specific nor was it predicted to target Dll1, Dnmt1, Mthfr, or Rbl2), Mishra et al, 2004. showed that DHFR is targeted by miR-24, which was found to be upregulated 1.36 times greater than control in TK-6 cells grown in FAD media (Marsit et al, 2006). This suggests that folate deficiency could initiate a negative feedback loop where overexpression of miR-24 suppresses DHFR, which would further decrease methyl-donor pools, exacerbating methyl deficiency (Bohnsack and Hirschi, 2004;Pufulete et al, 2005;Fig.…”
Section: Dhfrmentioning
confidence: 96%
“…Arsenite, which is known to activate nuclear factor-erythroid 2-related factor 2 (Nrf2) (Aono et al, 2003), affects miRNA expression in human lymphoblastoid TH-6 cells (Marsit et al, 2006). Cigarette smoking causes the down-regulation of many miRNAs in the lungs of both mice and rats (Izzotti et al, 2011) as well as human airway epithelial cells (Schembri et al, 2009).…”
Section: Vreugdenhil Et Al (2009) Have Reported That Rat and Human Glmentioning
confidence: 99%